ISLAM DAN KONSTITUSI INDONESIA 1945 - Fabian Fadhly (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2017)
The debate of certain circles who tend to appoint Indonesian Islamic society is desirous to restore the seven words of the 1945 Constitution, as a nation-state foundation like the Medina Charter which is the benchmark for how Islam behaves during the time of the Prophet Muhammad became a continuous growing issue. This allegation should not be raised continuously, as it is well known that Islam has a strong influence on the birth of the 1945 Act. This paper is put forward as an attempt to provide a proper understanding and meaning, regarding the influence of Islam on the emergence of the 1945 Constitution. In this paper is a historical method with a juridical approach, with the specification of literature research approach The influence of Islam in the 1945 Constitution came from the nine committee which has 8 members who are Muslims. Another influence is reflected in the sincerity of the emergence of editorial changes from the opening of the 1945 Constitution, from the initial agreement. The change is related to the loss of seven words known as the Jakarta Charter